Free radical oxidation and antioxidant defense in uterine myoma and endometrioid adenocarcinoma depending on its degree of differentiation - E. I. Surikova; E. M. Frantsiyants; I. V. Kaplieva; V. A. Bandovkina; L. A. Nemashkalova; I. V. Neskubina; T. I. Moiseenko; A. P. Menshenina; M. A. Rogozin; E. V. Verenikina; M. L. Adamyan (Южно-Российский онкологический журнал)
Purpose of the study. To evaluate the features of free radical oxidation (FRO) and the principal enzymatic and non-enzymatic links of antioxidant defense in proliferating tissues of benign myoma and malignant endometrioid adenocarcinoma (EA) with varying degrees of differentiation.Patients and methods. Patients who received surgical treatment for EA (n = 42) and uterine myoma (n = 14) were examined. Patients with stage Ia (n = 26) and stage Ib (n = 16) of disease were selected. 16 patients had highly differentiated (G1) EA, 12 had moderately differentiated (G2) EA, and 14 had low-differentiated (G3) EA. The activity of superoxide dismutase (SOD), catalase, glutathione peroxidase (GPx), glutathione transferase (GST), reduced glutathione (GSH), vitamins A and E, lipid peroxidation products diene conjugates (DC) and malondialdehyde (MDA) were determined colorimetrically in the tissues of EA, myoma and intact uterus.Results. Compared with the level in intact tissue, SOD decreased by 3.2 times and GST increased by 2.7 times in myoma (p < 0.01). Similar changes were noted for EA G1 – on average by 5.3 times (p < 0.01) and also DC increased by 2.2 times (p < 0.05). In EA G2 tissue, SOD and GPx activities were lower than in the intact tissue, by 5.7 and 4.5 times, respectively (p < 0.05), and lower GST, GPx and GSH than in the EA G1, by 4.9, 8.9 and 1.6 times, respectively (p < 0.05 – p < 0.01). In EA G3 tissue, there was an increase in GSH, GPx and GST from 1.5 to 7.1 times (p < 0.05 – p < 0.01) and lipid peroxidation products by an average of 2.5 times (p < 0.05), as well as a decrease in vitamins A and E by 2.9 and 4.6 times, respectively (p < 0.05) compared with the intact tissue. The tissue of the EA G2 had a minimal level of activity of the GSH-dependent system.Conclusion. The results reflect the differences in the mechanisms of proliferation regulation by FRO in myomas and in the EA tissue with changes in its differentiation. Knowledge of the characteristics of individual links in the regulation of FRO can play a certain role in the use of antioxidant therapy for benign or malignant tumors of the uterus.